PENGGUNAAN SMARTPHONE DIKALANGAN MAHASISWA FAKULTAS ILMU SOSIAL DAN ILMU POLITIK UNIVERSITAS RIAU - ", Resti; ", Indrawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study aims to look at the use of smartphones among students. As forthe principal problems in this study is the first, the reason students choose asmartphone as a means of communication and information students. Second, howthe use of a student who uses a smartphone.Based on the analysis that has been done, it can be concluded that thereasons students choose a smartphone as a means of communication andinformation that is used is using a smartphone is socially and lifestyle. They say tohave a smartphone, they can follow what is happening in the virtual world.Smartphones have a wide range of applications, especially social media such aspath and instagram. If they go for a walk or are hanging out with friends then theywill apdate place and social mediated photo so that others know what to do withsuch respondents respondents feel proud.In terms of time utilization of respondents said that the smartphone to giveeffect to their lectures. They said that for various reasons. Respondents said thatthe smartphone keeps them busy. Busy is meant here is the time to play theirsmartphones could forget the good time chatting disosial media, browsing andrespondents who are addicted to the games they download on their Smarphone.before has a smartphone that students taking the time to learn quite a lot, theyprefer to learn from the play and spend time to play but after having a smartphonefew respondents are willing to set aside time to learn every day of her.Key words: Smartphone, Use Of Time And Students